Trastorno del lenguaje y su repercusión en las relaciones interpersonales de un niño de 12 años de edad de la Unidad Educativa 5 de Octubre del cantón Echeandía - Rosero Gavilanez, Anthony Alejandro (2021)
The topic "Language disorder and its repercussion in the interpersonal relationships of a 12 year old boy of the Educational Unit 5 of October of the Echeandía Canton", was developed carrying out a qualitative methodology through the techniques of clinical interview, clinical history and psychometric tests (HTP - OTIS mental test), in which it was possible to visualize difficulties in the structuring and pronunciation of language, fulfilling the diagnostic criteria of a specific disorder of pronunciation F 80.0 according to the ICD 10. In addition, he presented difficulties in his interpersonal relationships and was a self-conscious child due to his fear of being embarrassed and discriminated for his poor use of language. We worked with a cognitive-behavioral therapeutic approach, achieving in the patient to develop a more assertive communication, among other results, such as greater development and adaptability in his environment.